Development and Initial Validation of the Performance Perfectionism Scale for Sport (PPS-S). (October 2016) - Hill, Andrew P.; Appleton, Paul R.; Mallinson, Sarah H.
Valid and reliable instruments are required to appropriately study perfectionism. With this in mind, three studies are presented that describe the development and initial validation of a new instrument designed to measure multidimensional performance perfectionism for use in sport (Performance Perfectionism Scale–Sport [PPS-S]). The instrument is based on Hewitt and Flett's (1991) model of perfectionism and includes self-oriented, socially prescribed, and other-oriented performance perfectionism. These dimensions encapsulate the features of Hewitt and Flett's dimensions but are focused on athletic performance rather than life generally. The three studies outline item generation and refinement, exploratory, confirmatory, and exploratory-confirmatory examination of factor structure, and initial assessment of construct validity in multiple samples of adolescent and young adult athletes. Findings suggest that the PPS-S is likely to be a reliable and valid measure of performance perfectionism in youth sport. As validation continues, we expect the instrument to have wider applicability for use in adults and other performance contexts (e.g., education and work).